A Study on Rodent Ectoparasites in the North district of Tehran, Iran - Pakdad, Kamran; Ahmadi, Nayeb Ali; Aminalroaya, Roya; Piazak, Noraier; Shahmehri, masoud (Archives of Advances in Biosciences, 2012)
Rodent ectoparasites seems have a main role in transmission of some zoonotic pathogens from commensal rats to human and pets such as leishmaniasis, plague, CCHF, etc. So rodents as the main reservoirs, are potential health dangers in human communities. The aim of this study was to determine the prevalence and frequency of identified ectoparasites in north of Tehran.Rodents were captured with live traps during 2007-2009. After transferring to the laboratory and identifying, their ectoparasites were collected and mounted for species identification by using valid keys. Sixty four rodents included two species: Rattus norvegicus (82.8%) and Mus musculus (17.2%) were captured. 1755 ectoparasites collected from 43 infested R.norvegicus were related to 5 genera and 6 species: Ornithonyssus bacoti (71.7%), Hoplopleura spp (17%), Hoplopleura oenomydis (11.3%), Polyplax spinulosa (3.8%), Nosopsyllus fasciatus (3.8%), and Ixodes ricinus (1.9%). 11 Mus musculus were free of ectoparasites. Among all arthropods, mites and ticks had the most (97.4%) and the least (0.1%) frequency in R.norvegicus, respectively. Also, Ornithonyssus bacoti was a prevalent species (71.7%) with mean abundant 32.2. I.ricinus with 1.9% prevalence was the least prevalent ectoparasites. 11 M.musculus were free of ectoparasites.